Znanje planincev in alpinistov o višinski bolezni - Slabe, Damjan (Šport (Ljubljana), 2023)
When physically active at the altitude of 2,500 meters or more, a person can develop one or more types of high-altitude illness (HAI): acute HAI, high-altitude cerebral oedema or high-altitude pulmonary oedema. The number of HAI cases is increasing. It is essential that an individual pre- vents HAI by good tour preparation and gradual acclimatisation. If problems do occur, first aid knowledge (FA) is of vital importance. FA is based on recognizing signs and symptoms of the illness early on. When HAI occurs, ascending has to stop. If the person’s condition does not improve, immediate descend and medical help are vital. The aim of the research was to find out the level of first aid knowledge of Slovene mountaineers and alpinists. 21% of 307 interviewees have already experienced one type of HAI. The alpinists and mountaineers who took part in the research, are well aware of the risks posed by high altitude. The majority also has a good knowledge of FA in the case of HAI. The percentage of right answers is around 90%. The knowledge of alpinists is in some cases statistically significantly better (p < 0,05) than that of mountaineers. The interviewees are less familiar with some symptoms and signs of different HAI types. Mountaineers and alpinists are aware that there is room for improvement, especially in the field of medicine application for treating and preventing HAI complications.
Keywords: akutna višinska bolezen; alpinizem; planinstvo; višinski možganski edem; višinski pljučni edem